2020
DOI: 10.1186/s12967-020-02315-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rapid weight loss on skeletal muscle in judo athletes

Abstract: Objective: To observe the effect of rapid weight loss (RWL) methods over 3 days on muscle damage in judokas. Methods: Eighteen judokas participated in this crossover study, meaning that judo athletes were subjected to exercise-only phase (4 days) and RWL phase (3 days). Subjects were tested for myoglobin, creatine kinase, aldolase, hemoglobin, and hematocrit values on seven consecutive days. These biomarkers served as indicators of acute muscle damage. Results: During the exercise-only phase, no significant ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 44 publications
7
21
0
4
Order By: Relevance
“…Moreover, the change in this variable was different in magnitude and sense between sexes (Figure 4). This reduction in what represents the metabolically active portion of the body is in agreement with the recent findings of Roklicer et al [45], who reported skeletal muscle damage to a significant extent in male jūdōkas who underwent a three-day RWL and strenuous exercise. Further research is needed to analyze the impact of RWL and RWG on muscle mass between males and females.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the change in this variable was different in magnitude and sense between sexes (Figure 4). This reduction in what represents the metabolically active portion of the body is in agreement with the recent findings of Roklicer et al [45], who reported skeletal muscle damage to a significant extent in male jūdōkas who underwent a three-day RWL and strenuous exercise. Further research is needed to analyze the impact of RWL and RWG on muscle mass between males and females.…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to this belief, a recent systematic review on the impact of RWL on judo athletes by Lakicevic et al [ 14 ] showed that the feelings of tension, anger, and fatigue significantly increased, while a decrease in vigor was demonstrated among judo athletes who practice RWL. As more and more emerging studies reveal harmful effects of RWL [ 9 , 34 38 ] which can even lead to lethal consequences [ 39 ], scientists suggested that this harmful practice should be banned from combat sports [ 29 ]. Moreover, alternative means of weight loss such as gradual weight loss at the rate of about 1 kilogram per week, elevated carbohydrate intake and emphasis on weight loss from fat depots have been proposed [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence a small number of studies have evaluated the role of higher intakes of protein coupled with a hypocaloric diet in competitive sports people. Despite the potential attraction of rapid weight loss strategies, the literature suggests that a slower rate of weight loss is preferable in this population group as this approach tends to prioritise fat loss over loss of lean tissue [ 94 , 95 , 96 ]. In addition, there is some suggestion that protein intakes significantly beyond current recommendations (1.6–2.4 g protein/kg body weight/d) [ 97 ] for athletic populations may result in improved body composition [ 95 ].…”
Section: Weight Loss In Sports Peoplementioning
confidence: 99%